FACTORS AFFECTING STUDENTS’ THESIS COMPLETION ON DEPARTMENT OF MANAGEMENT STIE MIKROSKIL - Ella Silvana Ginting; Apren Halomoan Hutasoit (UIN Sumatera Utara Medan, 2020)
This study is aimed to investigate the factors that influence the completion of students' final task, thesis. The research is causal comparative research which the data were obtained by directly surveying respondents through questionnaire. The population in this study were students who finishing their final task, who in semester 8 students students, with total sample size of 67. From the results of the hypothesis analysis simultaneously, a significant value was obtained of 0.000, which means that motivation to graduate on time, the ability to write scientific papers, and the quality of assignment guidance final possess effect on the completion of student final assignments. Partial analysis obtained a significant value of the motivation variable of 0.012, the variable of the ability to write scientific papers of 0.018, and the variable of quality of guidance of 0.000, which means that partially motivation, the ability to write scientific papers, and the quality of final assignment guidance stimulate bring effect on the completion of students' final tasks